Na-CMC and glycerine optimization in Binahong leaf extract (Anredera cordifolia) liposome gel and its burn wound healing activity - Immanuel, Handika; Branitasandini, Regina Epiphania Adhika; Branitasandini, Adhika; Arpan, Verdynant Augusto; Pebrianty, Sahara; Kerenhapukh, Miracle; Wardhani, Kresentia Ayu Kusuma; Yuliani, Sri Hartati (Universitas Ahmad Dahlan, 2025)
Burns represent a critical global health issue, contributing to considerable morbidity and mortality rates, particularly within the Southeast Asian region. The administration of appropriate burn therapy is essential to prevent infections and promote effective wound healing. The binahong leaf (Anredera cordifolia) represents a highly promising natural substance for burn therapy, attributed to its ursolic acid content, which is acknowledged for its wound healing properties. However, the limitation caused by its limited solubility and bioavailibility requires the use of nanoparticle technology, such as liposomes, to enhance its efficacy. The aim of this research was to determine an optimal formulation of gel containing liposome-encapsulated binahong leaf extract, with the goal of promoting burn wound healing and examining its in vivo wound healing activity. Histological analysis was employed to provide additional insights into the activity of the gel. The formulation was assessed through a factorial design, exploring various amounts of Na-CMC utilized as a gelling agent alongside glycerine employed as a humectant. The results were subsequently analyzed utilizing Design Expert v13 software. The gel’s viscosity, spreadability, and uniformity were assessed. Na-CMC increased viscosity while reducing spreadability, whereas glycerine had the opposite effect. The optimal formulation contained 2.78–4 g Na-CMC and 5–10 g glycerine. Statistical validation confirmed the model's accuracy. In vivo studies demonstrated that liposomal binahong gel significantly accelerated burn wound healing compared to controls. The results suggest that 10% binahong liposomal gel is a promising alternative for burn treatment.